Unjuk Kerja Destilasi Air Energi Surya - Ketut Puja, I Gusti; Rusdi Sambada, FA. Rusdi (Jurnal Energi Dan Manufaktur; Vol 5 No 1 (2012): Oktober 2012)
Clean water is daily needs for society, especially for drinking and cooking. Existing water sources often already contaminated with dirt, salt (sea water), heavy metals, bacteria or other harmful materials. The water in this condition can be detrimental to health if used for drinking or cooking, hence the water has to be rarefied first. There are many ways to purify contaminated water, one way is by distillation. Distillation process requires heat to evaporate the contaminated water before condensed and produce clean water. Thermal energy for distillation process can come from many sources, one of which is solar energy. The purpose of this study is to investigate the performance difference between solar powered water distillation that uses parabolic collector and reflector with solar powered water distillation without the use of parabolic collector and reflector (basic form). Distillated water will be tested in the laboratory to determine whether the water quality qualifies as drinking water or not after distillation process. Equipment which used in this study consisted of contaminated water tanks, distillation apparatus and distillated water storage. Distillation apparatus has a length of 1 meter and 0.5 meters wide. There are three variations on the distillation apparatus used i.e. distillation with reflector, distillation with parabolic collector and distillation without reflector and collector (basic form). Distillation appliance is equipped with water depth indicator. Water depth inside the distillation varied i.e. 5 mm, 7.5 mm, and 10 mm. The results showed a maximum of distilled water produced is 0.850 liter in 2 hours with an average efficiency of 49.2% produced by the distillation using reflector with 5 mm water depth. Maximum of distilled water yield with 10 mm water depth is 0.20 liter in 2 hours produced by distillation using parabolic collectors. Laboratory test stated that quality of distilled water can be accepted as drinking water.
Keywords: performance, distillation, reflectors, parabolic collectors